DENTAL PRENATAL CARE IN PRIMARY HEALTH CARE: PREGNANT WOMEN’S PERCEPTIONS AND INFORMATIONAL CHALLENGES IN A MUNICIPALITY OF MINAS GERAIS, BRAZIL (REMUNOM, 2026)
Pregnancy is a period marked by intense biological, psychological, and social changes, which require comprehensive care focused on the health of both the woman and the fetus. In this context, oral health plays a relevant role, since conditions such as dental caries and periodontal diseases may be associated with adverse pregnancy outcomes. Dental Prenatal Care is established as a fundamental strategy for promoting oral health and preventing conditions during pregnancy, especially within the scope of Primary Health Care (PHC). The present study aimed to assess the perceptions of pregnant women receiving care in the municipality of Iturama, Minas Gerais, regarding Dental Prenatal Care and self-reported oral health status. This was an observational, descriptive study with a quantitative approach, conducted with 24 pregnant women followed at a Primary Health Care Unit. Data collection took place between March and May 2023 through a structured questionnaire addressing oral hygiene habits, knowledge about oral health during pregnancy, perceptions of Dental Prenatal Care, and access to dental services. Data were analyzed descriptively using absolute and relative frequencies. The results showed that most pregnant women recognize the importance of oral health care during pregnancy and report regular attendance at dental appointments. However, limited specific knowledge about Dental Prenatal Care and the persistence of myths related to dental treatment during pregnancy were observed. It is concluded that, despite advances in public oral health policies, there is a need to strengthen educational actions and enhance the integration of dentists into prenatal care routines, in order to improve the quality of care, promote pregnant women’s autonomy, and consolidate comprehensive maternal and child health care within the Brazilian Unified Health System (SUS).